A Pilot Study of the Efficacy of the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders in Treating Posttraumatic Psychopathology: A Randomized Controlled Trial. Issue 3 (16th January 2021) - O'Donnell, Meaghan L.; Lau, Winnie; Chisholm, Katherine; Agathos, James; Little, Jonathon; Terhaag, Sonia; Brand, Rachel; Putica, Andrea; Holmes, Alexander C. N.; Katona, Lynda; Felmingham, Kim L.; Murray, Kim; et al.
Abstract: The Unified Protocol for Transdiagnostic Treatment of Emotional Disorders (UP) is an intervention that targets common mechanisms that maintain symptoms across multiple disorders. The UP has been shown to be effective across many disorders, including generalized anxiety disorder, major depressive episode (MDE), and panic disorder, that commonly codevelop following trauma exposure. The present study represented the first randomized controlled trial of the UP in the treatment of trauma‐related psychopathology, including posttraumatic stress disorder (PTSD), depression, and anxiety symptoms. Adults ( N = 43) who developed posttraumatic psychopathology that included PTSD, MDE, or an anxiety disorder after sustaining a severe injury were randomly assigned to receive 10–14 weekly, 60‐min sessions of UP ( n = 22) or usual care ( n = 21). The primary treatment outcome was PTSD symptom severity, with secondary outcomes of depression and anxiety symptom severity and loss of diagnosis for any trauma‐related psychiatric disorder. Assessments were conducted at intake, posttreatment, and 6‐month follow‐up. Posttreatment, participants who received the UP showed significantly larger reductions in PTSD, Hedges' g = 1.27; anxiety, Hedges' g = 1.20; and depression symptom severity, Hedges' g = 1.40, compared to those receiving usual care. These treatment effects were maintained at 6‐month follow‐up for PTSD, anxiety, and depressive symptom severity. Statistically significant posttreatment loss of PTSD, MDE, and agoraphobia diagnoses was observed for participants who received the UP but not usual care. This study provides preliminary evidence that the UP may be an effective non–trauma‐focused treatment for PTSD and other trauma‐related psychopathology. 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯: JOTS‐20‐0296.R2_O_Donnell (Agathos)_Cantonese Traditional Chinese 創傷後精神病理學中情緒障礙跨診斷治療的統一方案的試點研究: 一個隨機對照試驗 摘要: 情緒障礙跨診斷治療的統一方案(UP)是一項針對維持多種障礙症狀的共同機制的干預措施。情緒障礙跨診斷治療的統一方案已被證明對許多疾病有效, 包括廣泛性焦慮症、重度抑鬱症發作(MDEs)和恐慌症, 這些疾病通常在創傷暴露後發展。本研究是首個隨機對照試驗, 用於治療創傷相關的精神病理學, 包括創傷後壓力症(PTSD)、抑鬱症和焦慮症狀。成年人(N=129人) 在遭受嚴重傷害後出現創傷後精神病理學, 包括創傷後壓力症、MDE或焦慮症, 被隨機分配接受每週10‐14次、每次60分鐘的情緒障礙跨診斷治療的統一方案(n = 22)或常規治療(n = 21)。主要治療結果是創傷後壓力症症狀的嚴重程度, 次要結果是抑鬱和焦慮症狀的嚴重程度和診斷的喪失。在攝入量、治療後和治療後6個月的隨訪中進行評估。治療後, 與常規護理組相比, 接受情緒障礙跨診斷治療的統一方案的參與者在創傷後壓力症(Hedges' g = 1.27)、焦慮(Hedges' g = 1.20)和抑鬱(Hedges' g = 1.40)的症狀嚴重程度上有明顯的降低。這些治療效果在6個月的隨訪中對創傷後壓力症、焦慮和抑鬱症狀的嚴重程度都有保持。在治療後, 情緒障礙跨診斷治療的統一方案組的參與者在創傷後壓力症、重度抑鬱症和恐高症的診斷上有明顯的損失, 而在常規護理條件下則沒有。這項研究提供了初步證據, 表明情緒障礙跨診斷治療的統一方案可能是一種有效的非創傷性治療創傷後壓力症和其他與創傷相關的精神病理學。 Simplified Chinese 创伤后精神病理学中情绪障碍跨诊断治疗的统一方案的试点研究: 一个随机对照试验 摘要: 情绪障碍跨诊断治疗的统一方案(UP)是一项针对维持多种障碍症状的共同机制的干预措施。情绪障碍跨诊断治疗的统一方案已被证明对许多疾病有效, 包括广泛性焦虑症、重度抑郁症发作(MDEs)和恐慌症, 这些疾病通常在创伤暴露后发展。本研究是首个随机对照试验, 用于治疗创伤相关的精神病理学, 包括创伤后压力症(PTSD)、抑郁症和焦虑症状。成年人(N=129人) 在遭受严重伤害后出现创伤后精神病理学, 包括创伤后压力症、MDE或焦虑症, 被随机分配接受每周10‐14次、每次60分钟的情绪障碍跨诊断治疗的统一方案(n = 22)或常规治疗(n = 21)。主要治疗结果是创伤后压力症症状的严重程度, 次要結果是抑鬱和焦慮症狀的嚴重程度和診斷的喪失。在攝入量、治療後和治療後6個月的隨訪中進行評估。治療後, 與常規護理組相比, 接受情緒障礙跨診斷治療的統一方案的參與者在創傷後壓力症(Hedges' g = 1.27)、焦慮(Hedges' g = 1.20)和抑鬱(Hedges' g = 1.40)的症狀嚴重程度上有明顯的降低。這些治療效果在6個月的隨訪中對創傷後壓力症、焦慮和抑鬱症狀的嚴重程度都有保持。在治療後, 情緒障礙跨診斷治療的統一方案組的參與者在創傷後壓力症、重度抑鬱症和恐高症的診斷上有明顯的損失, 而在常規護理條件下則沒有。這項研究提供了初步證據, 表明情緒障礙跨診斷治療的統一方案可能是一種有效的非創傷性治療創傷後壓力症和其他與創傷相關的精神病理學。